Destination Marketing for Expatriates: A Case Study in Northern Cyprus - Mohammad Abuhjeeleh; Mohamed Dawood Shamout; Mohammad Tahseen Sleimi; Ibrahim Harazneh (African Journal of Hospitality, Tourism and Leisure, 2019)
With the intensifying competition in the global tourism industry, there has arisen an important need to enhance destination marketing initiatives in order to remain relevant. With effective marketing approaches, it is possible to increase the visitors that a destination receives, which is a beneficial outcome for any destination. Therefore, it becomes a critical concern for tourism stakeholders to identify the different methods that can be used to enhance or make destination marketing approaches more effective. This article explores one such possibility and that is the use of expatriates as a tool to enhance the marketing approaches as well as outcomes for any destination. Using the findings of a quantitative study carried out on expatriates in North Cyprus (Kyrenia City), the article discusses how these individuals can be an effective marketing tool. By using a questionnaire approach, with a study sample of 418 participants, the study sought to establish the general attitude i.e. positive or negative) as well as the experiential image that the expatriates had of Kyrenia city and North Cyprus as a tourism destination on the whole. The findings revealed that expatriates could also be used as a critical marketing tool by helping further establish the destination Image, from an outsider’s perspective as well as in identifying the positive destination attributes to be incorporated in the area’s tourism marketing initiatives.